2015
DOI: 10.1007/s10048-015-0442-4
|View full text |Cite
|
Sign up to set email alerts
|

A start codon CMT1X mutation associated with transient encephalomyelitis causes complete loss of Cx32

Abstract: X-linked Charcot-Marie-Tooth disease (CMTX1) results from numerous mutations in the GJB1 gene encoding the gap junction protein connexin32 (Cx32) and is one of the commonest forms of inherited neuropathy. Owing to the expression of Cx32 not only in Schwann cells but also in oligodendrocytes, a subset of CMT1X patients develops central nervous system (CNS) clinical manifestations in addition to peripheral neuropathy. While most GJB1 mutations appear to cause peripheral neuropathy through loss of Cx32 function, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 38 publications
0
20
0
Order By: Relevance
“…In other words, disruption of this function could be a necessary condition for florid CNS symptoms. This line of reasoning is supported by the recent report of recurrent florid symptoms in a patient carrying a Met1Ile mutation28, predicted to lead to complete loss of Cx32 protein52. This reasoning also suggests the possibility that complete loss of reflexive coupling in Schwann cells may lead to reduced peripheral nerve conduction velocities in patients with CNS + PNS mutants when compared to those with PNS only mutants, a possibility that could potentially be clinically assessed in the future.…”
Section: Discussionmentioning
confidence: 73%
“…In other words, disruption of this function could be a necessary condition for florid CNS symptoms. This line of reasoning is supported by the recent report of recurrent florid symptoms in a patient carrying a Met1Ile mutation28, predicted to lead to complete loss of Cx32 protein52. This reasoning also suggests the possibility that complete loss of reflexive coupling in Schwann cells may lead to reduced peripheral nerve conduction velocities in patients with CNS + PNS mutants when compared to those with PNS only mutants, a possibility that could potentially be clinically assessed in the future.…”
Section: Discussionmentioning
confidence: 73%
“…In fact, recent studies have found that under the influence of systemic inflammation transdominant effects of mutant Cx32 on other connexins can disrupt oligodendrocyte gap junctions, although oligodendrocyte dysfunction is further exacerbated by intracellularly retained mutants (eg, Thr55Ile) 40. Nevertheless, other studies have recently observed that even mutations associated with a complete loss of Cx32 can produce CNS dysfunction 41. Although a specific genotype-phenotype correlation between Cx32 mutation location (extracellular, intracellular or transmembrane) and WMLs has not been observed, recent studies suggest that the ability of Cx32 mutants to form gap junction plaques and produce adequate levels of junctional coupling in oligodendrocytes may relate to CNS manifestations 42.…”
Section: Discussionmentioning
confidence: 99%
“…It is highly unlikely that either could allow translation of a functional protein [Mentrup et al, 2011]. Most start codon mutations result in complete absence of the affected protein [Sargiannidou et al, 2015;Jinda et al, 2016].…”
Section: Amh Gene Mutationsmentioning
confidence: 99%